1998
DOI: 10.1007/s004200050256
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal and olfactory sensitivity: comparison of modalities and methods of measurement

Abstract: Objective: The principal objective was to chart sensitivity for human nasal irritation by alternative psychophysical methods, a common detection procedure vs. a nasal lateralization procedure that required the subject to indicate whether a vapor had stimulated the left or right nostril. This objective relates to the broader issues: a) whether subjects with normal olfaction (normosmics) can yield, through novel methodology, an index of sensitivity to nasal irritation comparable to that obtained from subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…This performance was considered 100 % detection. The ascending concentration order and an interstimulus interval of at least 45 sec to 1 min helped to minimize any potential changes in olfactory and/or trigeminal sensitivity 22 .…”
Section: Methodsmentioning
confidence: 99%
“…This performance was considered 100 % detection. The ascending concentration order and an interstimulus interval of at least 45 sec to 1 min helped to minimize any potential changes in olfactory and/or trigeminal sensitivity 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Perceptual differentiation between a strong smell and a weak nasal "feel" or irritation could prove difficult for a subject, and is likely to be biased by individual criterion (Cometto-Muñiz and Cain 1990). The task of nasal lateralization (or localization), whereby the subject seeks to identify the nostril (right or left) receiving the chemical stimulus when the other nostril simultaneously receives an identical puff of blank air, has proven a convenient tool to probe into detection of nasal chemesthesis unbiased by smell (Wysocki et al 1997;Cometto-Muñiz and Cain 1998;Dalton et al 2000). The approach relies on the observation that nasal lateralization is only achieved through trigeminal chemesthetic activation, not through olfactory stimulation (Schneider and Schmidt 1967;Kobal et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Bottles containing a blank or a chemical were consecutively presented to either the left or right eye, and the subject had to decide which bottle produced the stronger ocular sensation. Results they obtained from studies comparing eye thresholds between normosmics and anosmics show that nasal localization thresholds agree well with eye irritation thresholds (Cometto-Munˇiz and Cain 1998;ComettoMunˇiz et al 1998b). Opiekun et al (2003) applied the lateralization concept to the eyes.…”
Section: Reliability and Validity Of The Lt Proceduresmentioning
confidence: 70%
“…Contradictory findings have been reported. In a series of studies by Cometto-Munˇiz et al (1998, 1998a no significant differences were found between anosmics and normosmics in concentrations that yielded irritancy employing forced-choice procedures using homologous alcohols as the stimuli (Cometto-Munˇiz and Cain 1998) or terpenes (Cometto-Munˇiz et al 1998a;. However, in studies by Hummel et al (1996) and Kendal-Reed et al (1998), normosmics reported chemesthetic sensations at lower concentrations than did anosmics.…”
Section: Reliability and Validity Of The Lt Proceduresmentioning
confidence: 98%